X-rays are as effective as gamma-rays for the sterilization of Glossina palpalis gambiensis Vanderplank, 1911 (Diptera: Glossinidae) for use in the sterile insect technique - Bénéwendé Aristide Kaboré; Arooj Nawaj; Hamidou Maiga; Olga Soukia; Soumaïla Pagabeleguem; Marie Sophie Gisèle Ouédraogo/Sanon; Marc J. B. Vreysen; Robert L. Mach; Chantel J. de Beer (Scientific Reports, 2023)
Abstract An area-wide integrated pest management strategy with a sterile insect technique (SIT) component requires a radiation source for the sterilisation of male insects. Self-contained gamma irradiators, which were exclusively used in past SIT programmes, are now facing increasing constraints and challenges due to stringent regulations. As a potential alternative, new generation high output X-ray irradiators have been proposed. The feasibility of using X-ray irradiators was assessed by comparing the effects of both gamma- and X-ray irradiators on biological parameters of Glossina palpalis gambiensis (Vanderplank, 1911), that are important for SIT applications. The gamma irradiator Foss Model 812 and two X-ray irradiators, the Rad Source 2400 and the blood irradiator Raycell Mk2 were used. Glossina palpalis gambiensis males were exposed to radiation as pupae. A radiation dose of 110 Gy or above induced more than 97% sterility in females that mated with the irradiated males for all the irradiators. Adult emergence rate, flight propensity, survival and mating performance did not differ between gamma- and X-rays irradiators. These results suggest that irradiating pupae with a dose of 110 Gy is optimal for both gamma-and X-ray irradiators used in this study, to achieve a sterility of approximately 99%. Similar research on other tsetse species could gradually phase out the use of gamma-ray irradiators in favour of X-rays irradiators, especially for smaller SIT programmes.